PEMBUATAN SISTEM INFORMASI BRANDING DAN MARKETING KAWASAN USAHA MIKRO KECIL MENENGAH YANG BERSINERGI DENGAN KEGIATAN WISATA, PENDIDIKAN KELUARGA (DEWI PELAGA) DI CEMOROKANDANG MALANG - Mustika Mentari; Rosa Andrie Asmara; Eka Larasati Amalia; Vivin Ayu Lestari; Farida Ulfa; Mochamad Faisal Rahman; Almira Rahma Sabita; Muhammad Rizqi Ardiansyah; Aliza Rizqi Fitriana (P3M Politeknik Negeri Malang, 2024)
The geographical area of Cemorokandang village in Malang has a set of potential Small and Medium Enterprises (SMEs) that have been running for a long time but require technological support in branding and marketing. Currently, most SME groups in Cemorokandang village use the traditional method by entrusting the goods produced to shops around the area. The SMEs are in Dewi Pelaga (Desa Wisata Pendidikan Keluarga). Other potentials owned by Cemorokandang village that need to be managed are the potential for sports, tourism, and education potential. This potential needs to be promoted so that many people know it better. Therefore, it is necessary to have a branding and marketing information system that contains pages describing the potential of SMEs and other support such as sports, education, and tourism tracking places. The website that has been created has been tested, and results were obtained on the point that